Where was I? Taking alternative visual perspectives can make us (briefly) misplace our own. Issue 3 (March 2020) - Samuel, Steven; Legg, Edward W; Manchester, Callum; Lurz, Robert; Clayton, Nicola S
How do we imagine what the world looks like from another visual perspective? The two most common proposals—embodiment and array rotation—imply that we must briefly imagine either movement of the self (embodiment) or movement of the scene (array rotation). What is not clear is what this process might mean for our real, egocentric perspective of the world. We present a novel task in which participants had to locate a target from an alternative perspective but make a manual response consistent with their own. We found that when errors occurred they were usually manual responses that would have been correct from the computed alternative perspective. This was the case both when participants were instructed to find the target from another perspective and when they were asked to imagine the scene itself rotated. We interpret this as direct evidence that perspective-taking leads to the brief adoption of a computed perspective—a new imagined relationship between ourselves and the scene—to the detriment of our own, egocentric point of view.